The influence of biodegradable magnesium alloys on the osteogenic differentiation of human mesenchymal stem cells. Issue 12 (24th February 2014) - Li, Rachel W.; Kirkland, Nicholas T.; Truong, John; Wang, Jian; Smith, Paul N.; Birbilis, Nick; Nisbet, David R.
Abstract The postdegradation effect of pure Mg, Mg‐1Y, Mg‐5Al, and Mg‐2Ca alloys on the differentiation, proliferation and gene expression of human mesenchymal stem cells (hMSCs) was investigated. It was revealed that that Mg2+ ions result in an increase in cell proliferation. However, we observed a maximum concentration (approximately 8.0 × 10−4 M) that was favourable to ATP production, above which ATP production began to decrease. In contrast to proliferation, no maximum concentration for osteogenic differentiation was observed, with increasing concentration of Mg2+ ions resulting in an increase in osteogenic differentiation across the entire tested range. Interestingly, the Mg‐2Ca alloy had minimal effect on osteogenic differentiation, with Mg‐1Y and pure Mg having a superior effect on the proliferation and differentiation of hMSCs. This was also observed from gene expression data, where these alloys upregulated TGFβ‐1, SMAD4, FGF‐2, FGF‐10, and BMP‐2, while SOX‐2, SOX‐9, and TNF‐α were downregulated. Increased expression of TGFβ‐1, SMAD4, BMPs, and COLIA1 protein provided further evidence to support osteogenic differentiation and that the influence of the alloying extracts on differentiation may be via the SMAD signaling pathway. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4346–4357, 2014.